VD_FINDINFO HC / 2014 / 246 vom 18. Februar 2014 - VD Tribunal cantonal (2014)
MANDAT, DENTISTE, SOINS MÉDICAUX, OBLIGATION DE RENSEIGNER, FAUTE PROFESSIONNELLE | 398 al. 2 CO, 398 CO, 97 al. 1 CO, 97 CO